Genetic/epigenetic RNA dysregulation in type 2 diabetes mellitus complicated with ischemic heart disease - Sedkey, Eslam S.; Matboli, Marwa; Seadawy, Mohamed G.; Hegazy, Marwa G.A. (Frontiers in Endocrinology, 2025)
IntroductionDiabetes mellitus is a major independent determinant of cardiovascular morbidity. Therefore, we evaluated whether a molecular RNA panel comprising FZD5 and GTF2I could facilitate the early detection and discrimination of ischemic heart disease in individuals with type 2 diabetes mellitus.MethodsWe implemented a two-stage bioinformatics workflow to identify and validate two mRNA candidates associated with T2DM and IHD. Subsequently, we delineated non-coding RNAs linked to these transcripts and the pathways potentially implicated in T2DM complicated by IHD. Finally, we conducted a pilot case–control study and quantified the panel members by RT-qPCR in 56 patients with T2DM, 25 with IHD, 26 with combined T2DM+IHD, and 60 matched controls.ResultsDifferential expression analysis showed upregulation of hsa-miR-1976, FZD5, and GTF2I, accompanied by downregulation of LINC02210 in the T2DM+IHD group versus controls. The RNA panel achieved high discriminatory performance (AUC = 0.94) between T2DM+IHD and controls, highlighting its potential as a discriminatory tool.Discussionthis study identified clinically relevant non-coding RNA–based angiogenesis panel (FZD5, GTF2I mRNAs, hsa-miR-1976 and LINC02210 lncRNA) as a biomarker signature associated with type 2 diabetes mellitus complicated by ischemic heart disease.